Pembuatan Lip-Sync Menggunakan Metode Blendshape pada Animasi 3D - Zukharam Zukharam; Johan TM; Imam Muslem (Fakultas Ilmu Komputer Universitas Almuslim, 2025)
This study aims to produce virtual characters that can talk using a blendshape-based lip-sync technique. Generate lip-sync phoneme models in Indonesian on 3D-Animated characters. Applying Indonesian phoneme models to 3D-Animated characters. Make lip-sync research using the research's regional language, namely Indonesian. What makes it easier for animators, students and ordinary people who want to make 3D animation in Indonesian can be sampled for lip-syncing so that it can be applied with the resulting animation. The implementation stage is the stage which consists of the video creation process starting from the layout, R&D, modeling, texturing, rigging/setup, animation, VFX, lighting, to the rendering stage. The results showed that the final results were able to design lip-sync in this 3D cartoon animation according to the movement of the mouth with the sound that came out. In the lip-sync design process, we use a dope sheet which serves as a reference for mouth movements in animation. The end result is being able to set lip-sync through character control. The lip-sync process in the animation uses character control and is done only by moving the mouth control according to the predetermined dope sheet. The final result is able to present the story well based on the final result that follows the dope sheet